Evidence that the Ceratobasidium-like white-thread blight and black rot fungal pathogens from persimmon and tea crops in the Brazilian Atlantic Forest agroecosystem are two distinct phylospecies - Ceresini, Paulo C. [UNESP]; Costa-Souza, Elaine [UNESP]; Zala, Marcello; Furtado, Edson Luiz [UNESP]; Souza, Nilton L. [UNESP] (Sociedade Brasileira de Genética, 2012)
The white-thread blight and black rot (WTBR) caused by basidiomycetous fungi of the genus Ceratobasidium is emerging as an important plant disease in Brazil, particularly for crop species in the Ericales such as persimmon (Diospyros kaki) and tea (Camellia sinensis). However, the species identity of the fungal pathogen associated with either of these hosts is still unclear. In this work, we used sequence variation in the internal transcribed spacer regions, including the 5.8S coding region of rDNA (ITS-5.8S rDNA), to determine the phylogenetic placement of the local white-thread-blight-associated populations of Ceratobasidium sp. from persimmon and tea, in relation to Ceratobasidium species already described world-wide. The two sister populations of Ceratobasidium sp. from persimmon and tea in the Brazilian Atlantic Forest agroecosystem most likely represent distinct species within Ceratobasidium and are also distinct from C. noxium, the etiological agent of the first description of white-thread blight disease that was reported on coffee in India. The intraspecific variation for the two Ceratobasidium sp. populations was also analyzed using three mitochondrial genes (ATP6, nad1 and nad2). As reported for other fungi, variation in nuclear and mitochondrial DNA was incongruent. Despite distinct variability in the ITS-rDNA region these two populations shared similar mitochondrial DNA haplotypes.
Keywords: ecological speciation; fungal plant pathogens; host specialization; population divergence; phylogenetics